Mediator complex of the malaria parasite plasmodium falciparum associates with evolutionarily novel subunits - Iyer, Uthra Balasubramaniyan (2022)
The eukaryotic Mediator is a large and conserved multisubunit protein complex that directly contacts RNA polymerase II and impinges on multiple aspects of gene expression. The genome of the human malaria parasite Plasmodium falciparum has been predicted to encode several Mediator subunits. We provide physical evidence for the presence of a Mediator complex in P. falciparum by using coimmunoprecipitation and mass spectrometry to identify interaction partners of the highly conserved Mediator subunit PfMed31. We identify 11 of 14 predicted Mediator subunits and the products of two uncharacterized genes, PF3D7_0526800 and PF3D7_1363600, which are strongly associated with PfMed31. As expected, several additional interaction partners have known roles in the transcriptional control of gene expression and mRNA processing. Intriguingly, multiple interaction partners are implicated in endoplasmic reticulum function and the ER stress (ERS) response, suggesting crosstalk between the ERS response and the transcriptional machinery. Our results establish for the first time the physical presence of the Mediator complex within P. falciparum and strongly suggest that it plays both conserved and unique roles in the control of gene expression. Data are available via ProteomeXchange with the identifier PXD027640.